Evaluating Public University Service Quality and its Influence on Student Satisfaction and Loyalty: The Disjoint Two-Stage Approach - Luthfiana, Yusrina; Sujarwoto, Sujarwoto; Said, Moh. (Jurnal Manajemen Pelayanan Publik, 2025)
The growing competition between universities has led public universities to develop internal competitiveness, including student loyalty as a strategic asset. However, previous studies have shown inconsistencies in the results and have seldom applied higher-order constructs to analyze the public university service quality. This study evaluates university service quality and its impact on student loyalty, emphasizing the mediating role of student satisfaction. This study was conducted at the Faculty of Engineering, Universitas Negeri Jakarta. The data analysis technique employed PLS-SEM with the disjoint two-stage approach, which is more accurate in handling higher-order constructs on service quality. The findings indicate that public university service quality and student satisfaction influence student loyalty positively and significantly. Public university service quality also influences student satisfaction positively and significantly. Additionally, student satisfaction acts as a partial mediation between service quality and student loyalty. These findings underscore theoretically and practically that public universities should prioritize initiatives that improve service dimensions that impact student satisfaction and loyalty, such as students’ skill development. By integrating higher-order constructs for service quality, this study contributes to a methodological framework and actionable insights for administrators to optimize quality management in public universities.